Prevalence of domestic violence among married women doing unskilled manual work in a rural area of Trivandrum district - Divakaran Sreelatha, Deena; Girija, Nithya; Purandaran Vasanthamani, Benny; Samadarsi, Resmi; Bindhu, Anil; Jose, Regi; Leelavathy, Manju; ., Divija (International Journal Of Community Medicine And Public Health, 2021)
Background: Violence against women is an emerging problem in India. It has considerable adverse impact on the physical and mental health of women including suicidal tendencies. Violence against women and associated risk factors in many Indian communities remains unreported. This paper aimed to study the prevalence of physical, psychological, and sexual violence and risk factors of the women facing domestic violence. Methods: A community based cross sectional study was carried out in a rural area of Trivandrum district of Kerala state. Married women doing unskilled manual work were interviewed using a pretested validated questionnaire developed by Indu P V containing 20 items- 13 questions for assessing psychological violence, 5 for assessing physical violence and 2 for sexual violence. Results: The results showed that 26.76% of women experienced domestic violence. Poor educational qualification and having alcohol addiction in husbands were identified as important risk factors for experiencing domestic violence. Conclusions: Our data along with other sources show clearly that domestic violence is exacerbated by alcohol abuse and it may well be more prevalent in poor communities. Experience of domestic violence is more in women whose husbands are alcoholic. Multi sectorial response such as improving literacy, creating awareness regarding legal aid and screening the victims of violence at primary health centres, should be initiated to mitigate this public health issue.